2016
DOI: 10.1371/journal.pone.0154706
|View full text |Cite
|
Sign up to set email alerts
|

Biotype Characterization, Developmental Profiling, Insecticide Response and Binding Property of Bemisia tabaci Chemosensory Proteins: Role of CSP in Insect Defense

Abstract: Chemosensory proteins (CSPs) are believed to play a key role in the chemosensory process in insects. Sequencing genomic DNA and RNA encoding CSP1, CSP2 and CSP3 in the sweet potato whitefly Bemisia tabaci showed strong variation between B and Q biotypes. Analyzing CSP-RNA levels showed not only biotype, but also age and developmental stage-specific expression. Interestingly, applying neonicotinoid thiamethoxam insecticide using twenty-five different dose/time treatments in B and Q young adults showed that Bemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(156 citation statements)
references
References 91 publications
(109 reference statements)
7
149
0
Order By: Relevance
“…We know little about this gene other than it has been observed to be expressed in queen haemolymph (Sadd et al, ), and carries an odorant binding domain, suggesting that it may play a role in the transportation of semiochemicals such as odours and pheromones in the haemolymph. Its role may be conserved as a homologous gene in the whitefly Bemisia tabaci is also upregulated after exposure to the neonicotinoid thiamethoxam (Liu et al, ). Several general functions (Gene Ontology terms) were shared by workers and queens, including oxidation–reduction process, glucose metabolic process and single‐organism catabolic process (Supporting information Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…We know little about this gene other than it has been observed to be expressed in queen haemolymph (Sadd et al, ), and carries an odorant binding domain, suggesting that it may play a role in the transportation of semiochemicals such as odours and pheromones in the haemolymph. Its role may be conserved as a homologous gene in the whitefly Bemisia tabaci is also upregulated after exposure to the neonicotinoid thiamethoxam (Liu et al, ). Several general functions (Gene Ontology terms) were shared by workers and queens, including oxidation–reduction process, glucose metabolic process and single‐organism catabolic process (Supporting information Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Before the current study, the cDNA sequences of OBPs and CSPs had been only partly identified in B. tabaci (only eight OBP and 13 CSP sequences had been identified in MED, and only three CSP sequences had been identified in MEAM1), and especially in many cases, the sequences were incomplete (Li et al ., ; Liu et al ., , ; Wang et al ., , , ). In the current study, we obtained complete sequences for the eight OBPs and 19 CSPs in MEAM1 (Table ; Table ; Table S3) based on genome and antennae transcriptome data sets; these covered (and in some cases completed) all previously published sequences, and added six CSP sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al., 2014 b ; Zhu et al., 2016 a ); (17) H elicoverpa armigera and other species (Zhu et al., 2016 a ); (18) B ombyx mori (Xuan et al., ); (19) B emisia tabaci (G.X. Liu et al., 2014 a , 2016); P lutella xylostella (Bautista et al., ).…”
Section: Multiple Functions Of Obps and Cspsmentioning
confidence: 99%
“…Liu et al, 2014b;Zhu et al, 2016a); (17) Helicoverpa armigera and other species (Zhu et al, 2016a); (18) Bombyx mori (Xuan et al, 2015); (19) Bemisia tabaci (G.X. Liu et al, 2014aLiu et al, , 2016; Plutella xylostella (Bautista et al, 2015). while the only CSP found in reproductive organs of male locusts is also expressed in chemosensory structures, such as antennae, mouthparts and tarsi .…”
Section: (2) Pheromone Glands: Releasing Semiochemicalsmentioning
confidence: 99%